Factors Influencing Educational Adjustment among English Medium Students in Kottayam Diocese, Kerala, India: A Path Analytic Study - Varma, Parvathy (Journal of Education and Vocational Research, 2014)
The purpose of this study was to investigate the direct and indirect influence of parental involvement on Educational Adjustment among English Medium Students in Kottayam Diocese, Kerala, India, being mediated by Self-efficacy, English language anxiety, and mathematics anxiety. This quantitative research employed path analysis to investigate the study’s hypotheses. A total of 300 participants were selected via convenient sampling participated in the study. The path model showed that, the respondents’ their perceived level of parental involvement has a direct influence on their reported level of educational adjustment. Thus, the more they perceived their parents’ involvement in their academic life, the higher their reported level of educational adjustment. Parental involvement was also found to have an indirect influence on their educational adjustment, being mediated by their reported level of self-efficacy. Thus, the more the respondents perceived their parents’ involvement in their academic life, the higher their level of self-efficacy; subsequently, the higher their level of selfefficacy, the higher their reported level of educational adjustment. Self-efficacy was also found to be positively related to English language anxiety and negatively related to math anxiety. Thus, the higher the respondents’ reported level of self-efficacy, the higher their reported level of English language anxiety and the lower their reported level of math anxiety. Neither English language anxiety nor math anxiety was found to be significantly related to the respondents’ reported level of educational adjustment.